2023
DOI: 10.3390/jcm12062280
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Model Based on Optimized Radiomics Feature from 18F-FDG-PET/CT and Clinical Characteristics Predicts Prognosis of Multiple Myeloma: A Preliminary Study

Abstract: Objects: To evaluate the prognostic value of radiomics features extracted from 18F-FDG-PET/CT images and integrated with clinical characteristics and conventional PET/CT metrics in newly diagnosed multiple myeloma (NDMM) patients. Methods: We retrospectively reviewed baseline clinical information and 18F-FDG-PET/CT imaging data of MM patients with 18F-FDG-PET/CT. Multivariate Cox regression models involving different combinations were constructed, and stepwise regression was performed: (1) radiomics features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The PRISMA flowchart of the articles included in our review is reported in Figu The literature search identified a total of 31 studies. According to the aforementio eligibility criteria, 10 studies were included [17][18][19][20][21][22][23][24][25][26]. Among these, eight studies w retrospective and two prospective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRISMA flowchart of the articles included in our review is reported in Figu The literature search identified a total of 31 studies. According to the aforementio eligibility criteria, 10 studies were included [17][18][19][20][21][22][23][24][25][26]. Among these, eight studies w retrospective and two prospective.…”
Section: Resultsmentioning
confidence: 99%
“…All selected radiomic studies performed a statistical analysis in order to select the optimal/robust features. The total number of features initially extracted from each VOI, both for the CT and PET datasets, is summarized in Table 2 and ranged from 15 [25] to 1702 [19]; the most common features were SUVmax, shape, and first-order statistics, followed by textural features. After analysis, the selected features ranged from 3 [19] to 457 [22].…”
Section: Radiomics Assessmentmentioning
confidence: 99%
“…It is of great significance to choose appropriate imaging methods to perform iteratively for evaluating therapeutic response and guiding clinicians for follow-up treatment [17,25]. One of our recent studies showed that optimized radiomics feature from 18 F-FDG PET/CT images could predict progression of MM [26].…”
Section: Discussionmentioning
confidence: 99%
“…In hematological malignancies including multiple myeloma and acute leukemia, 18 F-FDG PET/CT radiomics-based ML analyses have been applied to identify skeletal metastases, predict diffuse infiltration in the bone marrow, or predict prognosis [ 125 128 ] (Table 7 ).…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%
“…The diagnostic accuracy of this model was significantly higher than that of visual analysis (0.886 vs. 0.686, p = 0.041). Ni et al [ 128 ] evaluated the ability of 18 F-FDG PET/CT radiomics-based ML analysis for predicting PFS after multiple myeloma treatment. Results showed that the ML model with the LASSO + cox regression algorithm trained using the combined clinical and PET/CT radiomics-based model had a higher predictive performance (C-index: 0.698) than the ML model with clinical data (C-index: 0.563) or PET/CT radiomics-based model (C-index: 0.651) alone.…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%